2002
DOI: 10.1103/physreva.65.053604
|View full text |Cite
|
Sign up to set email alerts
|

Continuous quantum measurement of a Bose-Einstein condensate: A stochastic Gross-Pitaevskii equation

Abstract: We analyze the dynamics of a Bose-Einstein condensate undergoing a continuous dispersive imaging by using a Lindblad operator formalism. Continuous strong measurements drive the condensate out of the coherent state description assumed within the Gross-Pitaevskii mean-field approach. Continuous weak measurements allow instead to replace, for timescales short enough, the exact problem with its mean-field approximation through a stochastic analogue of the Gross-Pitaevskii equation. The latter is used to show the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…However, this depletion scales completely differently than that caused by s-wave scattering and is strongly influenced by the presence of the resonance. The diffusion of atoms out of the condensate can also be interpreted as a quantum measurement-induced back-action process which stems from the dispersive atom-light interaction [5,19] and occurs even in phase contrast imaging of a condensate where the photon field is propagating in free space [46,47]. In a recent paper [18], we have shown that the depletion has a large steady-state value even in the limit of vanishing interaction strength U 0 .…”
Section: Correlations and Entanglementmentioning
confidence: 93%
“…However, this depletion scales completely differently than that caused by s-wave scattering and is strongly influenced by the presence of the resonance. The diffusion of atoms out of the condensate can also be interpreted as a quantum measurement-induced back-action process which stems from the dispersive atom-light interaction [5,19] and occurs even in phase contrast imaging of a condensate where the photon field is propagating in free space [46,47]. In a recent paper [18], we have shown that the depletion has a large steady-state value even in the limit of vanishing interaction strength U 0 .…”
Section: Correlations and Entanglementmentioning
confidence: 93%
“…The Hartree-Fock approximation for the evolution (31) can be applied to the master equation (33) using the techniques analyzed in Ref. [15].…”
Section: Multimode Systemmentioning
confidence: 99%
“…III and the techniques in Ref. [29], we find the master equation (33) gives the following functional NPW distribution evolution:…”
Section: Multimode Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…While this back action can be a useful resource [6][7][8][9][10][11][12], more often it leads to unwanted heating or decoherence [13][14][15][16][17]. We consider measuring the local density of atoms in a lattice.…”
Section: Introductionmentioning
confidence: 99%